Pengembangan Modul Pembelajaran Terintegrasi Nilai Islam dengan Pendekatan Saintifik pada Sistem Reproduksi Kelas XI SMA Negeri 13 Gowa - Said, Muh. Mas’ud; Hamansah; Hasanah, Ummul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop an integrated learning module of Islamic values ​​with a scientific approach to the reproductive system material and to test its validity, practicality, and effectiveness. The study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 34 students of grade XI KM 2 of SMA Negeri 13 Gowa. Data were collected using a validation sheet to assess product validity, teacher and student response questionnaires to measure practicality, and a learning outcome test to measure module effectiveness. Data were analyzed descriptively based on predetermined assessment criteria. The results showed that the developed module obtained a validity score of 3.8, categorized as very valid, a practicality score of 3.32, categorized as very practical, and an effectiveness level of 85%, categorized as very effective. These findings indicate that the module is suitable for use in learning. In addition, the integration of Islamic values ​​with a scientific approach can support the understanding of reproductive system concepts while strengthening the formation of positive attitudes in students in accordance with Islamic values.